Venovenous Extracorporeal Membrane Oxygenation for Negative Pressure Pulmonary Hemorrhage in an Elderly Patient - Kenichiro Ishida; Mitsuhiro Noborio; Nobutaka Iwasa; Taku Sogabe; Yohei Ieki; Yuki Saoyama; Kyosuke Takahashi; Yumiko Shimahara; Daikai Sadamitsu (Case Reports in Critical Care)
The patient in this case report was an 88-year-old male. Acute upper airway obstruction by food led to transient cardiac arrest, and negative pressure pulmonary hemorrhage (NPPH) occurred 1 hour after the foreign body obstruction. Using venovenous extracorporeal membrane oxygenation (ECMO) for severe acute respiratory distress syndrome resulting from NPPH, his respiratory state was recovered and hemoptysis stopped. NPPH is a life-threatening disease, the rapid recognition of which is required to initiate appropriate therapy. Although active hemorrhage might be a contraindication for ECMO, our experience showed this to be an effective treatment option. Moreover, our experience suggests that the application of ECMO to elderly patients should be considered on a case-by-case basis.